2008
DOI: 10.1016/j.jss.2007.12.762
|View full text |Cite
|
Sign up to set email alerts
|

All-trans-Retinoic Acid Attenuates Radiation-Induced Intestinal Fibrosis in Mice

Abstract: Our findings indicate that ATRA ameliorates irradiation-induced intestinal fibrosis. ATRA could be a novel approach in the treatment of fibrosis associated with chronic radiation enteritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Yeh et al 36 showed that 10 Gy whole‐body irradiation caused chronic intestinal fibrosis after irradiation. Linard et al 23 and Okoshi et al 24 established a murine model of late radiation‐induced intestinal fibrosis with 10 and 15 Gy abdominal irradiation, respectively. In the current study, we established an intestinal fibrosis model after a single dose of 10 Gy abdominal irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeh et al 36 showed that 10 Gy whole‐body irradiation caused chronic intestinal fibrosis after irradiation. Linard et al 23 and Okoshi et al 24 established a murine model of late radiation‐induced intestinal fibrosis with 10 and 15 Gy abdominal irradiation, respectively. In the current study, we established an intestinal fibrosis model after a single dose of 10 Gy abdominal irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal ileum was fixed in 4% buffered paraformaldehyde and embedded in paraffin. Sections (5 µm) were stained with hematoxylin and eosin (H&E) to evaluate histological changes and Masson's trichrome staining (MTS) to assess the severity of collagen deposition as previously reported 24 . The thickness of the submucosa was evaluated randomly in 5 fields in every sample.…”
Section: Methodsmentioning
confidence: 99%
“…Okoshi et al ’s [51] research shows that administration of ATRA attenuated irradiation-induced intestinal fibrosis and concomitantly reduced the expression of IL-6 and TGF-β1. They could determine from further in vitro studies that ATRA suppressed the trans-differentiation of irradiated intestinal fibroblasts and reduced the production of α-SMA and collagen.…”
Section: Role Of Ra In Diseasesmentioning
confidence: 99%
“…Radiation-induced intestinal disease has also been successfully modeled in mice (Followill et al, 1993; Okoshi et al, 2008) permitting informative strain variation investigations and the evaluation of genetic modifications on trait development. Firstly, important investigations in a mouse model have revealed dose dependent responses to develop in the intestines of C3Hf/Kam mice wherein the extent of early crypt depletion dictated the risk of obstruction (Followill et al, 1993).…”
Section: Post-irradiation Tissue Repairmentioning
confidence: 99%